2014
DOI: 10.1075/sl.38.4.08lew
|View full text |Cite
|
Sign up to set email alerts
|

The locative alternation in verb-framed vs. satellite-framed languages

Abstract: I propose a comparative analysis of the locative alternation in Polish and Spanish. I adopt a constructional theory of argument structure (Goldberg (1995)), according to which the locative alternation is an epiphenomenon of the compatibility of a single verb meaning with two different constructions: the caused-motion construction and the causative + with adjunct construction. As claimed by Pinker (1989), a verb must specify a manner of motion from which a particular change of state can be obtained in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…they admit only locative adjuncts. As argued by Boas (2006) and Lewandowski (2014b), the specificity of the verbal meaning seems to be correlated with its range of applications, that is, verbs with a less specific meaning can be used to describe a broader range of situations than verbs with a more precise semantics, whose compatibility with different constructional schemas (e.g., prefixes, PPs, etc.) is more restricted.…”
mentioning
confidence: 96%
“…they admit only locative adjuncts. As argued by Boas (2006) and Lewandowski (2014b), the specificity of the verbal meaning seems to be correlated with its range of applications, that is, verbs with a less specific meaning can be used to describe a broader range of situations than verbs with a more precise semantics, whose compatibility with different constructional schemas (e.g., prefixes, PPs, etc.) is more restricted.…”
mentioning
confidence: 96%
“…1 This finding is consistent with [1] Following conventional notations, we use an asterisk to indicate ungrammaticality. earlier work (Filipović, 2007;Lewandowski & Mateu, 2016) that demonstrated that prefixes, the typical locus of Path encoding in Polish (Kopecka, 2004;Lewandowski, 2014aLewandowski, , 2014bLewandowski, , 2020 show more restricted compatibility with verbs than particles and prepositional phrases, the typical locus of Path encoding in German (Bamberg, 1994;Harr, 2012).…”
Section: 1 I N T E R -T Y P O L O G I C a L V A R I A T I O Nmentioning
confidence: 97%
“…Since the verb typically conveys Manner of motion, satellites and prepositional phrases play an important role in the representation of motion events in Polish, making a distinction between Source-, Medial-, and Goal-oriented events (cf. Kopecka 2010Kopecka , 2012Lewandowski 2014;Łozińska 2018). Note, however, that our dataset also reveals the use of verbs such as oddalić się 'to move.away REFL' and zbliżyć się 'to approach, move toward (lit.…”
Section: Morphosyntactic Resources Used In Polishmentioning
confidence: 99%